The Association between ATM IVS 22-77 T>C and Cancer Risk: A Meta-Analysis - Zhao, Lin; Gu, Aihua; Ji, Guixiang; Zou, Peng; Zhao, Peng; Lu, Ailin (PLOS ONE, 2012)
Background and Objectives It has become increasingly clear that ATM (ataxia-telangiectasia-mutated) safeguards genome stability, which is a cornerstone of cellular homeostasis, and ATM IVS 22-77 T>C affects the normal activity of ATM proteins. However, the association between the ATM IVS 22-77 T>C genetic variant and cancer risk is controversial. Therefore, we conducted a systematic meta-analysis to estimate the overall cancer risk associated with the polymorphism and to quantify any potential between-study heterogeneity. Methods A total of nine studies including 4,470 cases and 4,862 controls were analyzed for ATM IVS 22-77 T>C association with cancer risk in this meta-analysis. Heterogeneity among articles and their publication bias were also tested. Results Our results showed that no association reached the level of statistical significance in the overall risk. Interestingly, in the stratified analyses, we observed an inverse relationship in lung and breast cancer. Conclusion Further functional research on the ATM mechanism should be performed to explain the inconsistent results in different cancer types.